Predicting and Assessing Progress in the Restoration of Ecosystems. Issue 2 (20th July 2017) - Sinclair, A.R.E.; Pech, Roger P.; Fryxell, John M.; McCann, Kevin; Byrom, Andrea E.; Savory, C. John; Brashares, Justin; Arthur, Anthony D.; Catling, Peter C.; Triska, Maggie D.; Craig, Michael D.; Sinclair, Tim J.E.; et al.
Abstract: Restoration of degraded landscapes has become necessary to reverse the pervasive threats from human exploitation. Restoration requires first the monitoring of progress toward any chosen goals to determine their resilience and persistence, and second to conduct in a comparable adjacent area but with less human impact the restoration of trophic structures and ecosystem processes to act as reference systems (controls) with which we compare the viability of the chosen goal. We present here the rationale and a method for predicting the trajectory of restoration and assessing its progress toward a predetermined state, the endpoint, using a restoration index . This assessment of restoration requires that we know when a predetermined endpoint has been achieved and whether the envisioned community of species and their interactions can be restored. The restoration index can use species' presence or density, and the rate of change of ecosystem processes. The index applies to trophic levels, functional groups, successional stages, alternative states, and novel ecosystems. Also, our method allows measurement of the resilience of ecosystems to disturbance, a desired property for conservation and management. We provide global examples to illustrate these points.